Impact of Women Empowerment through Microfinance: An Empirical Study - Md. Saidul Islam; Shake Farhan; Md. Akash; Md. Azharul Islam; Arifunnahar (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study attempts to investigate the relationship between microfinance and women empowerment concentrating on four independent variables and one dependent variable. To scrutinize these variables data has been collected from Satkhira district in Khulna from Bangladesh. Basically, the researchers use descriptive statistics, reliability statistics, ANOVA tables correlation and regression analysis in addition to demographic profiles as a research tool to examine the relationship between variables. Furthermore, the result shows that women empowerment has a positive relationship with payment procedures, Positive approach towards child rearing and Contribution to the economic growth but negative relation with Women position in the family / society. Therefore, it can be said that women empowerment is positively related to microfinance.